2021
DOI: 10.1108/par-09-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

Auditing in the time of COVID – the impact of COVID-19 on auditing in New Zealand and subsequent reforms

Abstract: Purpose This special issue paper aims to describe the early effects of COVID-19 on auditing in New Zealand, and the subsequent reforms that the authors expect will follow. Design/methodology/approach The authors use published sources to discuss the impact of COVID-19 on auditing, and potential reforms. Findings COVID-19 was at first expected to have a substantial impact on audit outcomes such as audit opinions. The effects that eventuated have been much less substantial so far. Nevertheless, the authors ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 14 publications
2
72
0
1
Order By: Relevance
“…466-469). It also seeks to contribute to accounting education literature in the context of COVID-19 because it is being consolidated before areas such as taxation (Sadiq and Krever, 2021;Wong et al, 2021), auditing (Hay et al, 2021) or financial markets (Naeem et al, 2021;Orhun, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…466-469). It also seeks to contribute to accounting education literature in the context of COVID-19 because it is being consolidated before areas such as taxation (Sadiq and Krever, 2021;Wong et al, 2021), auditing (Hay et al, 2021) or financial markets (Naeem et al, 2021;Orhun, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As for the results of a study by Albitar et al [8] in which content analysis and the authors' point of view were used based on the analysis of reports issued by some auditing companies, especially the four major auditing companies, they are consistent with the results of this study in terms of the significant impact of Covid 19 on several elements, namely, audit procedures, audit fees, audit Human capital, as well as employee salaries, which leads to a significant and profound impact on audit performance and quality. In their study, Hay et al [65] showed that the COVID19 crisis had a non-significant impact on audit reports and financial reports. On the other hand, our results are consistent with the results by Castka et al [5] which showed that the impact of COVID-19 on the audit practice was significant, as the traditional audit practice was reduced, which may require a long period to know the results of the non-traditional audit practice.…”
Section: -3-2-comparison With Other Studiesmentioning
confidence: 96%
“…Working from home is more flexible in work arrangements to improve work-life balance [6] and time efficiency during work [7], to keep operations rolling, and keep employees safe [17]. However, working from home makes it difficult for auditors to conduct direct inspections, communication becomes inflexible, causing auditors to have to collect more information about going concern clients' businesses, making it difficult to maintain their audit quality [11], [2]. Job motivation theory emphasizes the needs of individuals, their goals and expectations, or the personal results they find in rewards [18].…”
Section: Mediating Auditor Motivation On the Effect Of Work From Home...mentioning
confidence: 99%
“…An important area of audit quality is the issue of working from home due to the COVID-19 pandemic, such as: limiting the scope of the audit, making it difficult for auditors to conduct direct inspections, so they must collect more information about the company's going concern, to maintain their audit quality [11], affect audit fees, audit human resources, audit procedures, audit personnel salaries, and audit effort, which have a negative impact on audit quality [2].…”
Section: Introductionmentioning
confidence: 99%